REPRESENTASI STRATIFIKASI SOSIAL DALAM FILM ZOETE DROMEN (2023) KARYA ENA SENDIJAREVIC - Maharani, Najla; Pesulima, Barbara Elisabeth Lucia (UI Scholars Hub, 2025)
Film is a form of visual art that can shape public perceptions of various aspects of life, including social and cultural issues. One of the recurring themes in film is colonialism, which often represents issues such as racism and social stratification. These themes are reflected in the film Zoete Dromen (2023), directed by Ena Sendijarević, with a runtime of 1 hour and 42 minutes. The film narrates a conflict over inheritance within a sugar plantation-owning family, in which the entire estate is left to a child born from a relationship with a concubine. The research problem addressed in this study is: how is the representation of social stratification constructed in the film Zoete Dromen (2023) by Ena Sendijarević? The aim of this study is to describe the general depiction of social stratification in Zoete Dromen (2023) by analyzing the dialogue and visual elements among the characters. This research employs a descriptive qualitative method. It is grounded in Max Weber’s concept of social stratification, particularly his definitions of social class, social honor, and power. The concept of social stratification is further supported by Stuart Hall’s theory of cultural representation through the constructionist approach. The findings of this study indicate that the film portrays power as the central element of social relations, representing indigenous identity through language, symbols, and power dynamics. This research contributes to a deeper understanding of indigenous identity within the broader framework of social stratification as depicted in the film Zoete Dromen (2023).